Jump-Start Your Future Career - The, Star (The Star, 2020)
To be successful in the future, it is important to take the first step today as Mahatma Ghandhi once said, "The future depends on what you do today". If we want to walk a thousand miles, we need to start by taking the first steps, then the next one. Dear high school leavers, your future and your success could start with the University of London International.